Peningkatan Rasa Percaya Diri Siswa Tunagrahita Melalui Pembelajaran Terintegrasi Semiotik Dengan Media Buku Pop Up - Mu'jizatin Fadiana; Citra Dewi Rosalina (Universitas Lancang Kuning, 2020)
This service program is motivated by the lack of confidence in communicating retarded students in SLB C Autis Negeri Tuban. The lack of confidence in communication is caused by the lack of mastery and understanding of vocabulary. Therefore, by using a semiotic integrated learning design with pop-up book media it is hoped that it will increase the confidence of mentally retarded students, especially in communicating with others. This dedication program is carried out in the form of classroom action research involving 10 mild retarded students (C) and 5 moderate retarded students (C1). The team applies semiotic integrated learning with pop-up book media for six meetings. The results of this program indicate that there is an increase in confidence in mild and moderate retarded students at SLB C Autis Negeri Tuban. Confidence occurs through various processes, namely 1) self-performance, self-activity activities carried out in the learning process are the courage to appear in front of the class, tell stories, and answer questions. 2) there is a process of interaction and communication in learning activities between educators and students and fellow friends when the self-activity takes place. Thus, it can be concluded that through semiotic integrated learning with pop up book media can increase the confidence in communication retarded students.